Knowledge-Sharing In Rural And Suburban Community - Jatnika, Ratna (Advances in Social Sciences Research Journal, 2018)
This research is a cross sectional comparative study to know the difference of knowledge-sharingin Jelekong community which lives in a suburban area and Arjasari community which lives in a rural area in Bandung regency. The variables of this study are: Knowledge-sharing Intention The joy of knowledge-sharing Knowledge-sharing support ICT ability in knowledge-sharing Giving knowledge Mutual trust in knowledge-sharing Relationship builtfromknowledge-sharing Knowledge-sharing contribution Opportunistic behavior The analysis unit of this study are community leaders. The number of respondents in this study are 67 community leaders in Jelekong and 67 community leaders in Arjasari. The sampling technique was conducted using cluster sampling. The data obtained were processed using t-test to know the difference ofknowledge-sharing in Jelekong community and Arjasari community. The result of this research shows that there are 6 variables that have significant differencebetween Jelekong and Arjasari, they are: knowledge-sharing intention, the joy of knowledge-sharing, knowledge-sharing support, ICT ability in knowledge-sharing, giving knowledge, mutual trust in knowledge-sharing. While variables that do not differ significantly are: relationship built fromknowledge-sharing, knowledge-sharing contribution, opportunistic behavior.